Effectiveness of Early Spinal Fixation for Thoracolumbar Spine Fractures: A Quasi-Experimental Study - Sirirattanapan , Santi (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: We aimed to evaluate the effectiveness of early spinal fixation for thoracic and lumbar spine fractures. Methods: We employed a quasi-experimental design with prospective treatment and retrospective control groups (n=37 each). The treatment group received early spinal fixation within 72 hours according to the Royal College of Orthopedic Surgeons of Thailand guidelines, while the control group underwent late fixation after 72 hours. Data from patient medical records were analyzed using statistical tests. Statistical significance was set at p < 0.05. Results: We observed that the treatment group had a significantly lower morphine consumption compared with the control group within the first 24 hours postoperatively (mean difference 5.8, 95% Confidence Interval [CI] 2.4 to 9.3 and overall mean difference 2.8, 95%CI 0.2 to 5.6), and significantly higher scores in activities of daily living (ADL) at 1 week (mean difference 3.1, 95%CI 0.6 to 5.6) and 8 weeks (mean difference 4.0, 95%CI 1.1 to 6.8) postoperatively, with an overall mean difference of 3.5 (95%CI 0.7 to 6.3), indicating a faster functional recovery. Pain scores and the hospital length of stay did not differ significantly between the groups. The general medical expenses (mean difference 17,982, 95%CI 3,670 to 32,295) and total medical expenses (mean difference 20,174, 95%CI 2,415 to 37,933) were significantly higher in the treatment group, whereas implant costs did not differ significantly. Conclusions: Early spinal fixation surgery is effective in improving functional recovery for thoracic and lumbar spine fractures. Proper resource planning and further evaluation of cost-effectiveness are recommended.